The programme in which we calculate the motor's power, that are used in electrical transportation systems, by changing parameters of the motor's power formula and result curves - Senol, I; Gorgun, H; Aydeniz, MG (IEEE, 1998)
Factors, which effect directly the power of the motor which will be located into the electrical vehicle, are maximum speed( v(max)), travelling speed v(R)), distance between the stops (L), and acceleration of travelling ( b(r)). There is a relationship between these four factors which effect the motor power. We should keep in view the other factors which affect the power directly in order to calculate the motor power correctly. These are resistance of the travel, resistance of the road, and rate of cogwheel encircling etc. In the short distance transportation systems, because of constant speed the motor will be overheated and this can affect the choice of the motor power. But because of the short travel time this effect can be omitted. Startings and accelerations of the vehicle are more important than over-heating in the short distance transportation. This pecularity must not be regarded and we should add 15% of the calculated power to it. If we assume that the vehicle travel at 7% of speed and the destination is short. The equation will be; N-D/G=v(max)/27.4 root v(max).v(R)/L.b(R) [kW/Mp] While calculating the power, also overloading of the vehicle in the travel must be kept in view. By making tables which shows the over-load degrees we can make our calculations easily and using the curve of k = f ( I-A/I-D) which are drawn according to these tables, perpetual power can be calculated.
Keywords: Automation & Control Systems; Computer Science; Engineering; Optics; Telecommunications